2023
DOI: 10.3390/v15020445
|View full text |Cite
|
Sign up to set email alerts
|

I329L: A Dual Action Viral Antagonist of TLR Activation Encoded by the African Swine Fever Virus (ASFV)

Abstract: The African Swine Fever Virus (ASFV) is an economically important, large DNA virus which causes a highly contagious and frequently fatal disease in domestic pigs. Due to the acute nature of the infection and the complexity of the protective porcine anti-ASFV response, there is no accepted vaccine in use. As resistance to ASFV is known to correlate with a robust IFN response, the virus is predicted to have evolved strategies to inhibit innate immunity by modulating the IFN response. The deletion of virus host e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This study evaluated the safety, tolerability, and efficacy of experimental subunit vaccines that were formulated, with and without adjuvant, using a cocktail of 42 replication-deficient adenovirus-vectored multicistronic expression cassettes encoding ASFV antigens. As protective ASFV antigens are yet to be identified, immunization with a cocktail of the multicistronic expression cassettes was a strategy to deliver nearly 100% of the ASFV Georgia 2007/1 proteome to mimic antigen delivery by some ASFV mutants that have been shown to confer protection and if successful, this approach could fast track identification of the protective proteins needed for the development of rationally designed prototype subunit vaccines (8)(9)(10)(11)(12)(13)42). The multicistronic expression cassettes were stable after multiple passages of the recombinant adenoviruses as judged by expression of the FLAG tag at the C-terminal of the last gene in the cassette.…”
Section: Discussionmentioning
confidence: 99%
“…This study evaluated the safety, tolerability, and efficacy of experimental subunit vaccines that were formulated, with and without adjuvant, using a cocktail of 42 replication-deficient adenovirus-vectored multicistronic expression cassettes encoding ASFV antigens. As protective ASFV antigens are yet to be identified, immunization with a cocktail of the multicistronic expression cassettes was a strategy to deliver nearly 100% of the ASFV Georgia 2007/1 proteome to mimic antigen delivery by some ASFV mutants that have been shown to confer protection and if successful, this approach could fast track identification of the protective proteins needed for the development of rationally designed prototype subunit vaccines (8)(9)(10)(11)(12)(13)42). The multicistronic expression cassettes were stable after multiple passages of the recombinant adenoviruses as judged by expression of the FLAG tag at the C-terminal of the last gene in the cassette.…”
Section: Discussionmentioning
confidence: 99%
“…TheI329L protein is a type I transmembrane protein with 329 amino acids, which is relatively conserved in sequence and is expressed in late-stage viral infection ( Correia et al., 2023 ). Additionally, the I329L protein is homologous to the TLR family of proteins and its intracellular amino acid sequence shows 35% similarity to the BOX1 and BOX2 sequences of TLR3.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TLR3 and TLR7 were upregulated after ASFV infection, whereas TLR4 and TLR6 were downregulated [ 16 ]. Another study reported that ASFV I329L inhibits the activation of TLR3, TLR4, TLR5, TLR8, and TLR9 [ 17 ]. Moreover, Li et al showed that the ASFV-induced IL-1β production is dependent on TLR4 [ 18 ]; however, the role of TLR4 signaling in ASFV infection has not been reported.…”
Section: Introductionmentioning
confidence: 99%